PROSES COLLABORATIVE GOVERNANCE DALAM PENANGANAN STUNTING DI KELURAHAN BANDARHARJO KOTA SEMARANG - Putri Natasha, Anindita; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2025)
Stunting is a significant public health issue that has a serious impact on children's physical growth and cognitive development, ultimately affecting the quality of human resources in the future. Addressing stunting requires collaboration among various stakeholders through a process of collaborative governance. This study aims to describe the process of collaborative governance in handling stunting in Bandarharjo Village, Semarang City, and to identify the supporting and hindering factors in the implementation of this process. The research adopts a qualitative approach with a descriptive design. Data were collected through in-depth interviews with relevant stakeholders, direct field observations, and a literature review to examine relevant theories. The findings indicate that, although active collaborative efforts exist, the process of handling stunting in Bandarharjo Village is not yet optimal. Collaboration among the government, private sector, and the community has not been fully implemented or effective. Key supporting factors identified include government policies that support stunting reduction programs and the political commitment of local leaders. However, dominant hindering factors include low levels of trust among stakeholders, financial constraints, cultural barriers that hinder changes in dietary habits, and a lack of structured coordination and evaluation. This study recommends increasing the frequency of regular meetings to strengthen trust among stakeholders and enhance coordination. A measurable action plan with periodic evaluations is also essential, alongside culturally tailored approaches and nutritional 1 education to raise public awareness. Programs like Gemarikan can be optimized to promote protein consumption through education and access to nutritious food.